Impaired endothelial function in persons with obstructive sleep apnoea: impact of obesity. Issue 1 (9th October 2012) - Namtvedt, Silje K; Hisdal, Jonny; Randby, Anna; Agewall, Stefan; Stranden, Einar; Somers, Virend K; Røsjø, Helge; Omland, Torbjørn
Abstract : Objective: Obstructive sleep apnoea (OSA) and obesity are both associated with endothelial dysfunction, which precedes the development of atherosclerosis. As obesity is highly prevalent in OSA, we wanted to test the hypothesis that OSA is associated with endothelial dysfunction independently of obesity. Design: Cross-sectional, population-based study. Setting: Norwegian university hospital. Patients: Seventy-one subjects (median age 44 years, 35% female) were recruited from a population-based study in Norway. Participants were categorised as obese (body mass index (BMI) ≥30 kg/m 2 ), non-obese (BMI<30 kg/m 2 ) with OSA (apnoea–hypopnoea index (AHI)≥10), or non-obese without OSA (AHI<5). Interventions: None. Main outcome measures: Endothelial function measured by brachial artery ultrasound and expressed as percentage of flow-mediated dilation (FMD%). Results: When non-obese subjects without OSA were used as the reference (FMD% (mean±SD) 10.1±6.3), endothelial function was found to be impaired in subjects with OSA (FMD% 6.4±3.2) (p=0.003). FMD% did not differ between obese (6.0±3.4) and non-obese (6.7±3.1) OSA subjects (p=0.3). By univariate linear regression analysis, AHI, BMI, gender and baseline brachial artery diameter were significantly associated with FMD%. When these variables were entered into a multivariate model, only AHI was significantly associated with FMD%. Conclusions: OSA is associated with endothelial dysfunction independently of obesity and conventional risk factors.